2001
DOI: 10.1159/000047078
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Nitric Oxide Tissue Levels Correlate with Anoxia-Induced Gasping Activity in the Developing Rat

Abstract: Gasping is an important mechanism for survival that appears to be developmentally modulated by the glutamate-nitric oxide (NO) pathway. However, the temporal characteristics of NO brain tissue levels during gasping are unknown. We hypothesized that during anoxia-induced gasping, the gasping frequency would be closely correlated with caudal brainstem tissue NO concentrations in developing rats. Brainstem and cortical tissue NO levels were measured during anoxia using a voltammetric electrode in adult rats and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Alternatively, glutamate may participate in the production of gasping by acting on metabotropic, and not ionotropic, recep-tors. Furthermore, severe hypoxia is known to produce complex changes in the release of both excitatory and inhibitory neurotransmitters and neuromodulators in some brain regions, including brain stem regions associated with respiratory control (3,7,9,13,19,30,34,35); thus other excitatory neurotransmitters and/or neuromodulators (e.g., substance P; nitric oxide) in this region may participate in the production of hypoxia-induced gasping. Further investigation is required to assess these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, glutamate may participate in the production of gasping by acting on metabotropic, and not ionotropic, recep-tors. Furthermore, severe hypoxia is known to produce complex changes in the release of both excitatory and inhibitory neurotransmitters and neuromodulators in some brain regions, including brain stem regions associated with respiratory control (3,7,9,13,19,30,34,35); thus other excitatory neurotransmitters and/or neuromodulators (e.g., substance P; nitric oxide) in this region may participate in the production of hypoxia-induced gasping. Further investigation is required to assess these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from our laboratory have previously shown that N-methyl-Daspartate glutamate receptors are critically involved in particular components of gasp maturation (11), specifically in the early phases of respiratory activity that follow primary apnea. In addition, our laboratory has shown that increased neuronal nitric oxide synthase expression and activity occur with increasing postnatal age within the neural sites responsible for gasp generation and underlie some of the characteristic developmental changes in gasp activity (12,13). The overall changes in N-methyl-D-aspartate receptor and neuronal nitric oxide synthase expression associated with intermittent hypoxia during fetal and early postnatal life are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…By the same token, postnatal switches in the expression of neurochemicals, such as neurotransmitter receptor subunit switches, may be paralleled by comparable “switches” in physiological responses during specific period or periods of postnatal development. A few possible switches to consider include: GABA A receptor and chloride cotransporter-mediated switch from depolarizing to hyperpolarizing transmission (discussed above), a change in phrenic nerve output from irregular to regular (Zhou et al, 1996), a switch from a triphasic to a monophasic gasping response (Gozal and Torres, 2001), a switch in the hypoxic response from mainly a central to both central and peripheral chemoresponsive mechanisms (Saetta and Mortola, 1987) in conjunction with significant maturational changes in carotid body chemoreceptors postnatally (Donnelly, 2005), and a rearrangement of the sympathetic and vagal control of the heart rate (Mills, 1978). The precise timing of these switches needs to be investigated further, as most studies focused on a few selected postnatal days, and profound changes can occur in a relatively short time span, sometimes even in a single day (see above).…”
Section: Physiological Correlates Of a Critical Period Of Respiratmentioning
confidence: 99%